2019
DOI: 10.1371/journal.pone.0211677
|View full text |Cite
|
Sign up to set email alerts
|

Bed bugs (Cimex lectularius L.) exhibit limited ability to develop heat resistance

Abstract: The global population growth of the bed bug, Cimex lectularius (L.), is attributed to their cryptic behavior, diverse insecticide resistance mechanisms, and lack of public awareness. Bed bug control can be challenging and typically requires chemical and non-chemical treatments. One common non-chemical method for bed bug management is thermal remediation. However, in certain instances, bed bugs are known to survive heat treatments. Bed bugs may be present after a heat treatment due to (i) abiotic factors associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Similarly, it has been shown that adult bed bugs can survive short duration heat exposure at 45.0 °C, but if the exposure period is increased, complete mortality can be achieved. 7,8 Heat can also quickly cause mortality in bed bugs on the exterior of luggage, with high levels of control being achieved in 6 min at 75.0 °C. 9 Also, bed bugs that have fed more recently are able to tolerate higher temperatures, as it has been shown that physiological death occurs at 44.1 °C in insects starved for 21 days, but bed bugs that were starved for 9 days were able to survive until 45.2 °C.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, it has been shown that adult bed bugs can survive short duration heat exposure at 45.0 °C, but if the exposure period is increased, complete mortality can be achieved. 7,8 Heat can also quickly cause mortality in bed bugs on the exterior of luggage, with high levels of control being achieved in 6 min at 75.0 °C. 9 Also, bed bugs that have fed more recently are able to tolerate higher temperatures, as it has been shown that physiological death occurs at 44.1 °C in insects starved for 21 days, but bed bugs that were starved for 9 days were able to survive until 45.2 °C.…”
Section: Introductionmentioning
confidence: 99%
“…10 Heat is used for bed bug control because it is lethal to insecticide resistant populations, can be used in sensitive areas where pesticides cannot be applied and when deployed properly, high temperatures can kill all bed bugs harboring in cryptic locations within a domicile. [6][7][8][9][10] There are three different ways that heat is used for bed bug control: (i) steam (~100.0 °C) can be applied topically to bed bug containing furniture, [5][6][7][8][11][12][13][14] (ii) bed bug harboring items can be heated in compartmentalized units or tents (> 50.0 °C), 9 or (iii) entire apartments or homes infested with bed bugs can be heat treated (> 50.0 °C). [5][6][7][8][11][12][13] During a commercial whole domicile heat treatment, heated air (~60.0 °C) is circulated to raise and maintain temperatures at or above 50.0 °C for at least 6 to 8 h to ensure an even temperature distribution and cause complete mortality of all bed bug life stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such efforts include research that requires the laboratory breeding of thousands of animals not only for testing insecticides and critical temperatures (e.g. Ashbrook, Scharf, Bennett, & Gondhalekar, 2017, 2019; Gaire, Scharf, & Gondhalekar, 2019; Puckett, McDonald, & Gold, 2013; Romero, Potter, Potter, & Haynes, 2007), reviewed by Hase, 1930; Usinger, 1966; Feldlaufer, O'Connor, & Ulrich, 2018) but also for screening for novel control targets such as symbionts (Balvín, Roth, Talbot, & Reinhardt, 2018; Goodman, 2018), neuropeptides (Predel, Neupert, Derst, Reinhardt, & Wegener, 2018) or communication molecules (Gries, Zhai, Lewis, Britton, & Gries, 2018). All these targets are closely linked to the two major aspects that alter bedbug physiology, feeding and mating.…”
Section: Introductionmentioning
confidence: 99%
“…Eradication of a bed bug infestation requires integrated pest management (IPM) that considers all available pest control techniques. Bed bug management may include the use of insecticides, desiccant dust, heat, freezing techniques, mechanical removal, and monitoring ( Pereira et al 2009 , Kells and Goblirsch 2011 , Koganemaru and Miller 2013 , Romero et al 2017 , Lee et al 2018 , Ashbrook et al 2019 ). Prevention should be an integral part of IPM, which involves education, creating bed bug unfriendly surroundings, informing staff and travelers, specific luggage storage, and in some cases, the use of repellent products ( Singh et al 2014 , Romero et al 2017 ).…”
mentioning
confidence: 99%